Effectiveness Of Puzzle Game As Distraction Method To Reduce Anxiety Of Hopitalized Children Aged 3-6 Years Old (Case Study At Gondo Suwarno Hospital Semarang) - Sutarmi, Sutarmi (Jurnal Studi Keperawatan, 2024)
Hospitalization is often interpreted as a punishment for children, then the child will feel embarrassed, afraid, anxious, thus causing the child to act aggressively, angry, rebellious, often ask questions, not want to eat, not cooperate until he loses control and limited activities which makes treatment difficult. hospitals could be hampered. This study is to provide nursing care for children by applying puzzle play therapy to reduce anxiety in preschool aged children (3-6 years) with hospitalization at RSUD dr. Gondo Suwarno Ungaran. The design of this scientific work uses a case study approach based on inclusion and exclusion criteria. Observation of anxiety levels using the Preschool Anxiety Scale Revised (PASR) questionnaire. Â The results was focused on the nursing problem raised was to reduce anxiety in pre-school children (3-6 years) with hospitalization. The intervention is based on SIKI and SLKI with EBNP intervention in the form of providing puzzle playing therapy. This puzzle playing therapy lasts for 3 days with a duration of 10-15 minutes in one meeting. Giving EBNP shows a decrease in anxiety so that nursing problems can be resolved. There were 3 respondents aged 3-6 years, female and male, hospitalized. 3 clients experience moderate anxiety, appear fussy, quiet, avoid eye contact, appear tense. After the puzzle therapy intervention was carried out, the three clients experienced mild anxiety, appeared calm, and felt less tense. It can be concluded that puzzle game was effective to reduce anxiety of the hospitalized children from moderate to mild anxiety.Keyword: Â anxiety, preschool children, puzzle game, hospitalization